Influence of rearing system on the productive, carcass and meat quality attributes among three genotypes of native lambs in Bangladesh - Hashem , MA; Mamun, MAA; Arafath, MS; Numan, AA; Hossain, MM (Meat Research, 2023)
The aim of this study was to evaluate the productive performance, carcass traits and meat quality of native lambs of Bangladesh under two rearing system. Total 30 animals were taken for productive, carcass and meat quality attributes evaluation from three regions (Jamuna Basin, Barind Region and Coastal Belt); and total 18 animals were considered for evaluating productive, carcass and meat quality parameters for two treatment groups (T1= Grazing, T2= Stall Feeding) from each of three regions. Statistical analysis was conducted by SAS where statistical model was 3*2 factorial experimental model in CRD. DMRT was conducted for mean comparison and 5% level of significance was considered for analyses. Both genotype and rearing system had significant effect (p<0.05) on body weight at different rearing systems. Among all genotypes grazing lambs had the highest body weight than stall feeding lambs where CBL shows higher body weight compared to JBL and BRL. The ADG of grazing lambs were found significantly (p<0.01) higher than stall feeding lambs. Dressing % (46.80) was higher in grazing lambs. Genotype and rearing system had significant effect (p<0.05) on blood, head, shoulder, loin wt.% except skin, viscera, leg, pluck, Neck, rack, and shank where only genotype had significant effect but effect of rearing system was non-significant (p>0.05). Genotype and rearing system had significant effect (p<0.05) on heart, and spleen weight%. CP%, EE% and Ash% were found higher in grazing lambs whereas DM was higher in stall feeding. DL, Ultimate pH, cooked pH and WHC% were higher in grazing lambs whereas CL% were higher in stall feeding. Grazing lambs showed higher tenderness, juiciness and overall acceptability whereas stall feeding lambs showed higher color and flavor. Instrumental color values L*, a*, b* and saturation index were found significantly (p<0.05) higher in grazing lambs. Superiority of JBL over CBL and BRL in terms of overall productive, carcass and meat quality attributes largely varied in different genotypes for different rearing systems. It may be concluded that grazing group had positive effects on productive performance, carcass traits, proximate components, physicochemical, sensory evaluation and instrumental color values in three genotypes of native lambs of Bangladesh where JBL performs better compared to CBL and BRL.